Slopy Area Land Technology (Salt) - a Viable Alternative to Shifting Cultivation - Patnaik, Bijay Ketan (Indian Forester, 1998)
A pilot case study on the approach of Slopy Area Land Technology (SALT) for tackling shifting cultivation problem in the hilly terrain of Tangarapada village of Keonjhar District, Orissa, was carried out since 1992-93. The result is quite encouraging and the 4 beneficiaries in fact are now getting a sustainable flow of income both from agriculture crop and horticultural plantation.